A detailed clinical analysis of 13 patients with AUTS2 syndrome further delineates the phenotypic spectrum and underscores the behavioural phenotype. Issue 8 (13th April 2016) - Beunders, Gea; van de Kamp, Jiddeke; Vasudevan, Pradeep; Morton, Jenny; Smets, Katrien; Kleefstra, Tjitske; de Munnik, Sonja A; Schuurs-Hoeijmakers, Janneke; Ceulemans, Berten; Zollino, Marcella; Hoffjan, Sabine; Wieczorek, Stefan; et al.
Abstract : Background: AUTS2 syndrome is an 'intellectual disability (ID) syndrome' caused by genomic rearrangements, deletions, intragenic duplications or mutations disrupting AUTS2 . So far, 50 patients with AUTS2 syndrome have been described, but clinical data are limited and almost all cases involved young children. Methods: We present a detailed clinical description of 13 patients (including six adults) with AUTS2 syndrome who have a pathogenic mutation or deletion in AUTS2 . All patients were systematically evaluated by the same clinical geneticist. Results: All patients have borderline to severe ID/developmental delay, 83–100% have microcephaly and feeding difficulties. Congenital malformations are rare, but mild heart defects, contractures and genital malformations do occur. There are no major health issues in the adults; the oldest of whom is now 59 years of age. Behaviour is marked by it is a friendly outgoing social interaction. Specific features of autism (like obsessive behaviour) are seen frequently (83%), but classical autism was not diagnosed in any. A mild clinical phenotype is associated with a small in-frame 5′ deletions, which are often inherited. Deletions and other mutations causing haploinsufficiency of the full-length AUTS2 transcript give a more severe phenotype and occur de novo. Conclusions: The 13 patients with AUTS2 syndrome with unique pathogenic deletions scattered around the AUTS2 locus confirm a phenotype–genotype correlation. Despite individual variations, AUTS2 syndrome emerges as a specific ID syndrome with microcephaly, feeding difficulties, dysmorphic features and a specific behavioural phenotype.